Brooke-Spiegler Syndrome - an underrecognized cause of multiple familial scalp tumors: report of a new germline mutation - Pinho, AC (2016)
BACKGROUND: Brooke-Spiegler syndrome (BSS) is probably an underdiagnosed genodermatosis that predisposes for the development of cylindromas, spiradenomas and trichoepitheliomas mainly of the head and neck. Wide phenotypic variability regarding the number and type of lesions can be observed within a family. Mutations of the CYLD gene are identified in the vast majority of cases and play a key role in BSS pathogenesis. MAIN OBSERVATIONS: Two first degree relatives with numerous erythematous telangiectatic nodules of the scalp present for decades, with recurring tendency regardless the multiple previous excisions. Histopathological review of the lesions revealed predominantly "spiradenocylindromas" in the proband and cylindromas in her sister. The suspicion of BSS was confirmed after detection of a new nonsense germline mutation of CYLD (c.1783C>T pGln 595*) in the proband. CONCLUSIONS: BSS diagnosis can be challenging and is based on clinical-pathological correlation, positive familial association and identification of CYLD mutations. CYLD exerts antineoplastic effects by downregulating intracellular NF-κB signalling pathways. The reported mutation affecting the ubiquitin-specific protease domain leads to a truncated and catalytically inactive enzyme. Despite the expanding list of CYLD mutations no firm genotype-phenotype correlation is known so far. Early recognition and treatment of BSS avoid disfiguring changes like "turban tumor".